The Aftermath of 9/11: The Struggles of Arab-American Muslims in Laila Halaby’s Once in a Promised Land - Mukhtar, Umar; Az-zahra, Fatima Ayu; Amanda, Rifa Alya (Litteratura: Jurnal Bahasa dan Sastra, 2024)
This research discusses the impact of the 9/11 tragedy on Muslims in America, especially Arab-American Muslims. The two major characters as an Arab-American Muslim get bad behavior from the surrounding community who have already given bad prejudice against them. This is clear because the perpetrators of the 9/11 tragedy were Arab terrorists who acted in the name of Islam for their actions. This qualitative study uses it as a methodological framework to explore whether there is resistance from Muslims who receive bad treatment from society. The data and evidence that has been collected comes from the novel Once in a Promised Land, as well as from studies that intersect with the topic of this research. Edward Said's Orientalism Theory is used to reveal orientalist prejudice against Arab-Americans by engaging with Postcolonial Studies. The novel challenges orientalist prejudice by showing Islamic values through its major character. This resulted in findings which revealed that the bad prejudice about Islam caused by the 9/11 tragedy was countered by good character traits. Hence, the findings show that although the two major characters get a lot of prejudice and bad behavior from the surrounding community, this novel depicts them as opponents of oriental prejudice by showing the nature of Muslims which reflects the Islamic Values.